Udder quality is moderately heritable in Hereford cattle - Bradford, Heather L.; Moser, Daniel W.; Bormann, Jennifer M.; Weaber, Robert L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2014)
Udder quality is an important factor related to cow longevity and calf performance. Cows with tighter udder suspension and smaller teats tend to have greater longevity. When cows stay in the herd longer, fewer replacement heifers need to be developed to maintain herd size. Pendulous, poorly suspended udders and large teats are difficult for newborn calves to nurse, and additional labor might be required to assist those calves. Cows with poor udder quality can have increased calf mortality because the calf struggles to nurse and consumes colostrum later. Because many beef producers sell calves by the pound at weaning, poor udder quality can have a negative impact on profit. The dairy industry has selected for udder quality for many years. Udder traits are generally moderately heritable in dairy cattle, but limited research has been done in beef cattle. Beef producers would benefit from genetic selection tools for improving udder quality, especially for herds where udder quality affects calf performance. Our objective was to estimate the heritabilities and genetic correlations for udder quality traits in Hereford cattle. American Hereford Association members have been reporting udder scores for a number of years. The American Hereford Association initially began collecting an overall udder score, which combined all udder characteristics into a single score. In 2008, the Beef Improvement Federation developed udder scoring guidelines, including scores for both udder suspension and teat size. By August 2008, the American Hereford Association began using these new guidelines and collected udder suspension and teat size scores instead of the overall scores. All scores were recorded on a 1 to 9 scale, with scores of 9 considered ideal. Cows are scored at calving and could have multiple records throughout their lifetimes.
Keywords: Beef; Calf performance; Udder quality; Teat size; Genetics; Cows